2019
DOI: 10.15835/nbha47411651
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of WRKY Family Genes and Analysis of Their Expression in Response to Abiotic Stress in Ginkgo biloba L.

Abstract: Ginkgo biloba is widely planted, and the extracts of leaves contain flavonoids, terpene esters and other medicinal active ingredients. WRKY proteins are a large transcription factor family in plants, which play an important role in the regulation of plant secondary metabolism and development, as well as the response to biotic and abiotic stress. In our study, we identified 40 genes with conserved WRKY motifs in the G. biloba genome and classified into groups I (groups I-N and -C), II (groups IIa, b, c, d, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Interestingly, the expression of the ginkgo leaves’ WRKYs is regulated by many phytohormones, such as ABA, SA, MeJA, GA, and ETH. These hormones regulate ginkgo terpene lactone synthesis by affecting WRKYs [ 37 , 42 ]. A KEGG database comparison revealed that differentially expressed genes of different Se treatments were mainly concentrated in phenylpropanoid biosynthesis, phytohormone signal transduction, terpene synthesis and other related pathways ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression of the ginkgo leaves’ WRKYs is regulated by many phytohormones, such as ABA, SA, MeJA, GA, and ETH. These hormones regulate ginkgo terpene lactone synthesis by affecting WRKYs [ 37 , 42 ]. A KEGG database comparison revealed that differentially expressed genes of different Se treatments were mainly concentrated in phenylpropanoid biosynthesis, phytohormone signal transduction, terpene synthesis and other related pathways ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a total of 89 CoWRKY genes were identified in diploid and wild progenitor of C. oleifera , greater than in some woody species such as C. sinensis (56) ( Wang et al., 2019 ), Pinus massoniana (31) ( Yao et al., 2020 ), Cunninghamia lanceolate (44)( Zeng et al., 2019 ), and Ginkgo biloba (40)( Cheng et al., 2019 ), but fewer than in Arachis hypogaea (158, allo-tetraploid) ( Zhao et al., 2020 ), strawberry (222, allo-octoploid) ( Zhou et al., 2022 ), and soybean(174, paleopolyploidy) ( Yang et al., 2017 ). By inference, cultivars of C. oleifera , as a hexaploid, were predicted to harbor much larger numbers of WRKY proteins in the genome.…”
Section: Discussionmentioning
confidence: 90%
“…The WRKY proteins of following species were retrieved from prior studies: Arabidopsis thaliana ( Eulgem et al, 2000 ), Brassica napus ( He et al, 2016 ), Malus domestica ( Qin et al, 2022 ), Camellia sinensis ( Wang et al, 2019 ), Cucumis sativus ( Chen et al, 2020b ), Physcomitrella patens ( Rensing et al, 2008 ), Theobroma cacao ( Silva Monteiro de Almeida et al, 2017 ), Medicago truncatula ( Kumar et al, 2016 ), Cyanidioschyzon merolae ( Dou et al, 2014 ), rice ( Oryza sativa ) ( Ramamoorthy et al, 2008 ), Ginkgo biloba ( Cheng et al, 2019 ), Chlamydomonas reinhardtii ( Rinerson et al, 2015 ), Vitis vinifera ( Guo et al, 2014 ), Solanum melongena ( Yang Y. et al, 2020 ), Azolla filiculoides ( Zhao et al, 2021 ), Salvinia cucullate ( Zhao et al, 2021 ), Selaginella moellendorffii ( Rinerson et al, 2015 ), Moringa oleifera ( Zhang et al, 2019 ), Solanum lycopersicum ( Huang et al, 2012 ), Sorghum bicolor ( Baillo et al, 2020 ) and Populus trichocarpa ( Jiang et al, 2014 ). The evolutionary relationships of these species were determined according to the PGDD database ( Lee et al, 2013 ) and previous study ( Liu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%